Prevalence and characteristics of foramen huschke: Cone beam computed tomography study (Annals of Medical Research, 2021)
Aim: Aim: Foramen Huschke (FH) is an anatomical variant seen on the anterior aspect of external auditory canal. Aim of this study is to define the prevalence and characteristics of FH in a group of patients using cone beam computed tomography (CBCT).Materials and Methods: Study included 600 temporal bones of randomly selected 300 patients who had undergone CBCT examination. CBCT images were analyzed for the presence of FH. Patient’s age, genderwhen FH was present, laterality, and dimensions of FH were recorded. Frequency of FH and the relationship between FH and, patient age, gender and FH dimensions were evaluated with statistical analysis. Results: Of the evaluated 300 patients FH frequency was 18.7%. Thirteen percent of the evaluated 600 temporal bones had FH and a female predominance was observed (p=0.0160.05). Average age of patients was found to be lower than patients without FH (p0.01). Mean dimensions of FH was 2.19 ±0.66 mm and 2.37±0.73 mm on sagittal and axial planes, respectively. No statistically significant relationship between FH dimensions and gender and lesion laterality was observed. There was a weak negative correlation between patient age and FH dimensions on axial plane (r=-0.253; p=0.0250.05).Conclusion: FH is a common anatomical variation of the external auditory canal and is more common in females. Patient age is an important factor in FH presence. Average defect size is around 2mm and dimensions of FH may be related with patient age.